IFRS IMPLEMENTATION AND FINANCIAL REPORTING QUALITY: EVIDENCE FROM UZBEKISTAN AND TRANSITION ECONOMIES - Qodirjonov Dilshodjon Qosimjon o‘g‘li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
In the context of globalization and economic liberalization, ensuring transparency and comparability of financial information has become a critical priority for emerging markets. The adoption of International Financial Reporting Standards (IFRS) aims to harmonize accounting practices and strengthen investor confidence.In Uzbekistan, the transition to IFRS officially began with Presidential Decree PF-5959 (February 24, 2020), which mandated IFRS-based reporting for large enterprises from 2021 onward. This reform coincided with similar transitions in Kazakhstan, Georgia, and Ukraine, marking a shift from rule-based national systems toward principle-based international frameworks.However, while regulatory progress has been rapid, the impact of IFRS adoption on actual reporting quality, transparency, and investor perception remains under-researched in Uzbekistan. Globally, empirical findings are mixed: while some studies (Barth et al., 2008; Ahmed et al., 2013) suggest IFRS improves information quality, others highlight challenges related to enforcement, institutional capacity, and auditor independence.This research seeks to bridge that gap by examining how IFRS implementation influences financial reporting quality in Uzbekistan, and by comparing findings with other transition economies that have undergone similar reforms.